The final girl support group - Hendrix, Grady (New York : Berkley, 2021)
"A fast-paced, thrilling horror novel that follows a group of heroines to die for, from the brilliant New York Times bestselling author of The Southern Book Club's Guide to Slaying Vampires. In horror movies, the final girl is the one who's left standing when the credits roll. The one who fought back, defeated the killer, and avenged her friends. The one who emerges bloodied but victorious, a victim and a hero. But after the sirens fade and the audience moves on, what happens to her? Lynnette Tarkington is a real-life final girl who survived a massacre twenty-two years ago, and it has defined every day of her life since. And she's not alone. For more than a decade she's been meeting with five other actual final girls and their therapist in a support group for those who survived the unthinkable, putting their lives back together, piece by piece. That is until one of the women misses a meeting and Lynnette's worst fears are realized-someone knows about the group and is determined to take their lives apart again. But the thing about these final girls is that they have each other now, and no matter how bad the odds, how dark the night, how sharp the knife . . . they will never, ever give up"--
Description based on print version record and CIP data provided by publisher; resource not viewed.